Kegiatan Penghijauan Lingkungan Gereja Melalui Pemberdayaan Jemaat Gereja Advent Kota Wamena - Rein Edward Yohanes Rumbiak; Sumiyati Tuhuteru; Yosafat Oagay; Emius Mirin (Jurnal Pengabdian Masyarakat (abdira), 2022)
Reforestation is implemented as an effort to create a beautiful area with a variety of environmental benefits such as maintaining the balance of water system in nature, preventing the occurrence of soil erosion and earth erosion. Reforestation is an effort to plant trees and plants in a place that is considered to be a growing flower of the plant. Green land is aimed to restore, and increase the productivity of the land that condition is damaged to be able to function optimally through environmental activities. The purpose of this dedication is as a process of scientific implementation for the community in reducing the form of air pollution in the church, preventing flooding and motivating citizens to care about the church environment where the worship. The results of this activity demonstrate the enthusiasm of the church congregations in an effort to create a clean, green and healthy church environment beginning with the cleansing of the environment, planting of trees, and awareness to maintain and preserve the environment through the implementation of the Community devotion activities. Reforestation is one of the important activities done in reducing the impact of the environmental crisis.